Homestead Farming Systems and their Impact on Livelihood of the Ethnic Minority People of Northwestern Hilly Area of Bangladesh - Mahzabin, Iffat Ara; Nawata, Eiji (Fundamental and Applied Agriculture, 2023)
Homestead farming has been playing an important role in the livelihood of the ethnic minority groups, including Garo and Koch in Bangladesh. It secures the integrated production of crops, trees and livestock in the premises of household and its surrounding areas. The northwestern hill forest is decreasing day by day at an alarming rate. In the context of the prevailing shortage of fuel wood and excessive deforestation, the existing homestead farming system of the ethnic people needs to be strengthened for their better livelihood. From this point of view, the study was conducted in two villages of Jhenaigati Upazila (the smallest administrative unit of Bangladesh) of Sherpur District of Bangladesh to find out changes of the homestead farming systems and their impact on people’s livelihood. Fourteen different homestead farming systems were categorized by the presence of different livestock populations. A total of 109 plant species from 60 families were recorded in the study area. Among them 28 percent were identified as fruit species, 20 percent medicinal, 13 percent vegetable, 10 percent timber, 10 percent ornamental, 5 percent spices and 5 percent fuel wood. Fruit tree species like mango and jackfruit showed dominance. This dominance may be associated with the multipurpose usage of fruit trees as food, fuel wood, fodder and timber. About 20% households replaced their cassava plantation area with a mixed garden of fruits and timber yielding species. Exotic timber yielding species and medicinal plants were grown for commercial purposes as well as daily consumption. About fifty percent households had mixed garden of fruit and timber yielding species. Almost all households planted exotic timber yielding species in their mixed gardens. Medicinal plants were grown commercially, which was not practiced ten years back in the study area. The livestock species found in the homestead were cattle, chicken, duck, pig, goat, sheep and rabbit. Households having large homestead area had a tendency to raise more diversified livestock species. Pig rearing has shown a declining trend due to high price of piglets.